Объяснение:
4. x₃=20 x₅=-40 S₉=?
{x₃=x₁+2d=20
{x₅=x₁+4d=-40
Вычитаем из второго уравнения первое:
2d=-60 |÷2
d=-30.
x₁+2*(-30)=20
x₁-60=20
x₁=80.
x₉=x₁+8d=
S₅=80+8*(-30)=80+(-240)=80-240=-160.
S₉=(80+(-160)*9/2=(80-160)*9/2=-80*9/2=-40*9=-360.
ответ: S₉=-360.
5. S₃=168 S₄₊₅₊₆=21 S₅=?
{S₃=b₁+b₁q+b₁q²=168 {b₁*(1+q+q²)=168
{S₄₊₅₊₆=b₁q³+b₁q⁴+b₁q⁵ {b₁q³*(1+q+q²)=21
Разделим второе уравнение на первое:
q³=1/8=(1/2)³
q=1/2.
b₁*(1+(1/2)+(1/2)²)=168
b₁*(1+(1/2)+(1/4))=168
b₁*(1³/₄)=168
(7/4)*b₁=168
b₁=168*4/7=24*4
b₁=96.
S₅=96*(1-(1/2)⁵)/(1-(1/2))=96*(1-(1/32))/(1/2)=96*(31/32)/(1/2)=
=(96*31/32)/(1/2)=31*3/(1/2)=93*2=186.
ответ: S₅=186.
ответ: 120*a^4*b^9*c^2
Решаем по действиям:1. 4*2.5=10 X2.5 _ _4_ 10 2. a*a^2=a^3 a*a^2=a^(1+2) 2.1. 1+2=3 +1 _2_ 33. (-10*a^3*b^3)*(-4*a*b^3)=-10*a^3*b^3*(-4*a*b^3)4. 10*a^3*b^3*(-4*a*b^3)=-10*a^3*b^3*4*a*b^35. 10*4=40 X10 _4_ _ 406. a^3*a=a^4 a^3*a=a^(3+1) 6.1. 3+1=4 +3 _1_ 47. b^3*b^3=b^6 b^3*b^3=b^(3+3) 7.1. 3+3=6 +3 _3_ 68. -(-40*a^4*b^6)=40*a^4*b^69. 40*3=120 X40 _3_ _ 12010. b^6*b^3=b^9 b^6*b^3=b^(6+3) 10.1. 6+3=9 +6 _3_ 9
Решаем по шагам:1. (-10*a*b^3*a^2)*(-4*a*b^3)*c^2*3*b^3 1.1. 4*2.5=10 X2.5 _ _4_ 10 2. (-10*a^3*b^3)*(-4*a*b^3)*c^2*3*b^3 2.1. a*a^2=a^3 a*a^2=a^(1+2) 2.1.1. 1+2=3 +1 _2_ 33. (-10*a^3*b^3*(-4*a*b^3))*c^2*3*b^3 3.1. (-10*a^3*b^3)*(-4*a*b^3)=-10*a^3*b^3*(-4*a*b^3)4. (-(-10*a^3*b^3*4*a*b^3))*c^2*3*b^3 4.1. 10*a^3*b^3*(-4*a*b^3)=-10*a^3*b^3*4*a*b^35. (-(-40*a^3*b^3*a*b^3))*c^2*3*b^3 5.1. 10*4=40 X10 _4_ _ 406. (-(-40*a^4*b^3*b^3))*c^2*3*b^3 6.1. a^3*a=a^4 a^3*a=a^(3+1) 6.1.1. 3+1=4 +3 _1_ 47. (-(-40*a^4*b^6))*c^2*3*b^3 7.1. b^3*b^3=b^6 b^3*b^3=b^(3+3) 7.1.1. 3+3=6 +3 _3_ 68. 40*a^4*b^6*c^2*3*b^3 8.1. -(-40*a^4*b^6)=40*a^4*b^69. 120*a^4*b^6*c^2*b^3 9.1. 40*3=120 X40 _3_ _ 12010. 120*a^4*b^9*c^2 10.1. b^6*b^3=b^9 b^6*b^3=b^(6+3) 10.1.1. 6+3=9 +6 _3_ 9